[tex]\bf \left.\qquad \qquad \right.\textit{negative exponents}\\\\
a^{-{ n}} \implies \cfrac{1}{a^{ n}}
\qquad \qquad
\cfrac{1}{a^{ n}}\implies a^{-{ n}}
\qquad \qquad
a^{{{ n}}}\implies \cfrac{1}{a^{-{{ n}}}}
\\\\\\
and\qquad \quad a^{\frac{{ n}}{{ m}}} \implies \sqrt[{ m}]{a^{ n}} \qquad \qquad
\sqrt[{ m}]{a^{ n}}\implies a^{\frac{{ n}}{{ m}}}\\\\
-------------------------------\\\\
[/tex]
[tex]\bf \cfrac{3x^{-\frac{4}{3}}}{3(1+2x^{\frac{5}{3}})}\implies \cfrac{3}{3}\cdot \cfrac{1}{x^{\frac{4}{3}}}\cdot \cfrac{1}{(1+2x^{\frac{5}{3}})}\implies \cfrac{1}{x^{\frac{4}{3}}(1+2x^{\frac{5}{3}})}[/tex]
[tex]\bf \cfrac{1}{x^{\frac{4}{3}}+2x^{\frac{5}{3}}x^{\frac{4}{3}}}\implies \cfrac{1}{x^{\frac{4}{3}}+2x^{\frac{5}{3}+\frac{4}{3}}}\implies \cfrac{1}{x^{\frac{4}{3}}2x^{\frac{9}{3}}}\implies \cfrac{1}{x^{\frac{4}{3}}+2x^3}
\\\\\\
\cfrac{1}{\sqrt[3]{x^4}+2x^3}\implies \cfrac{1}{x\sqrt[3]{x}+2x^3}\implies \cfrac{1}{x(\sqrt[3]{x}+2x^2)}[/tex]